Managing language issue in second language storytelling. (October 2020) - Lee, Yo-An; Hellermann, John
Abstracts: Conversational storytelling involves producing multiple turns that are sequenced consecutively to form a connected whole. Producing a connected story is a challenging task for second language (L2) speakers because their language use may generate repairs of various kinds. In this regard, L2 tellers have the dual obligation of moving their stories forward while managing language issues that may interrupt the progress of their telling. The present study was designed to trace how language issues are handled during L2 storytelling and what relevance this has on the topical themes of the stories-in-progress. The data were taken from two corpora in which nonnative speakers of English engaged in storytelling sessions. The findings revealed the diverse ways in which language issues are exposed or embedded through repair sequences. While tellers' uncertainty regarding language use often prompts repairs, these repairs are subject to their contingent decisions to resume their stories. This study provides insight into how language moments are configured into storytelling sequencing, a topic that has received limited attention in applied linguistics. Highlights: L2 tellers manage two competing forces, intersubjectivity to handle repairs and progressivity to move stories forward. Language matters are exposed on some occasions or embedded into subsequent turns on others. The character of language matters are often determined in reference to the topical coherence of the stories in progress.